Phase Transition at High Heating Rate and Strain Rate During Maraging Steel C250 Grinding. Issue 13 (2nd October 2016) - Ding, Zishan; Li, Beizhi; Shao, Yamin; Liang, Steven Y.
Abstract : In this study, maraging steel kinetics of both diffusion-controlled and diffusionless phase transitions under thermo-mechanical conditions was predicted using a physics-based model via the investigation of heating rate, stain rate, and contact zone temperature during grinding. It was assumed that high heating rate and high strain rate will affect phase transition. The theory of phase transition nucleation was combined with analysis of heating rate, stain rate, and contact zone temperature to predict phase transition during the grinding. The effects of heating rate and strain rate on phase transition were verified through maraging steel grinding experiments, X-ray diffractometry, and regression analyses. The results of post-grinding phase volume fractions of martensite and ferrite were compared with the results predicted from the neural network model, and models without consideration of heating rate or strain rate. Validation tests proved that the proposed physics-based model successfully predicted the occurrence and extent of phase transition associated with heating rate and strain rate. This physics-based model can be used to reduce phase transition during grinding of maraging steel, or to cause a predefined phase transition by controlling the thermo-mechanical loading.